Integrated manufacturing of direct 3D-printed clear aligners - Rajasekaran, Abirami; Chaudhari, Prabhat Kumar (Frontiers in Dental Medicine, 2023)
The inception of laboratory work for the construction of a removable, tooth-moving appliance by sectioning teeth from the malocclusion model to align them with wax and achieve minor dental correction has evolved into a state of digital planning and appliance manufacturing for a wide spectrum of malocclusions. The groundbreaking technology of directly printing clear aligners has drawn the interest of clinicians and researchers in the orthodontic community today. This workflow enables the development of an in-house aligner system with complete control over desired aligner thickness, extent, and attachments; it is also technically resource-efficient with greater accuracy by excluding all the intermediate steps involved in the thermoforming method of manufacturing. This promising exploratory subject demands to be well-received with further research-based improvements. This article intends to summarize the digital orthodontic workflow and the literature evidence.